DIFFERENT USE OF PROBIOTICS ON THE GROWTH AND WATER QUALITY OF VANNAMEI SHRIMP (Litopenaeus vannamei) - Achmad Hidayah Guantoro; Hany Handajani; Ganjar Adhywirawan Sutarjo (Universitas Muhammadiyah Malang, 2023)
Vannamei shrimp (Litopenaeus vannamei) cultivation in the last 5 years has become excellent. Water quality is a determining factor for the success of cultivation. The purpose of this study was to determine the effect of using different probiotics on the growth and water quality of vannamei shrimp ( Litopenaeus vannamei ). This research was conducted at UPT. BAPL Bangil and UPT. Labkeskanling Pasuruan was held on 29 June – 29 July 2021. This study used a completely randomized design with 4 treatments and 3 repetitions with a dose of Control, As-One (0.009%), GDM (0.09%), and Epicin-D (0 ,09%). The research results were analyzed using ANOVA. The data obtained from the variance was then further tested with the BNT test. Treatment 4 (Epicin-D) had the highest value (absolute weight 28.24 gr, absolute length 14.71 cm, specific growth 7.88 gr) and treatment 1 (control) had the lowest value (absolute weight 20.73 gr, absolute length 8.92 cm, specific growth 6.11 gr). The results of observations of water quality during the study were temperature 27.70 oC – 28.30 oC, pH 7.50 – 7.52, dissolved oxygen 5.44 mg/l – 5.50 mg/l, salinity 9.88 ppt – 9.94 ppt, Ammonia 0.25 mg/l, nitrite 0.91 mg/l, and nitrate 55.21 mg/l. TPC results for Treatment 1 (2.5 x 108 Cfu/ml and 2.9 x 109 Cfu/ml), Treatment 2 (2.5 x 108 Cfu/ml and 2.4 x 109 Cfu/ml), Treatment 3 (2.5 x 108 Cfu/ml and 8.9 x 108 Cfu/ml), and Treatment 4 (2.5 x 108 Cfu/ml and 2.9 x 109 Cfu/ml). Based on the results of this study, it can be concluded that the observed parameters (absolute weight growth, absolute length, and specific growth rate) were significantly different but vannamei shrimp survival was not significantly different.